HUBUNGAN KONFORMITAS TEMAN SEBAYA DENGAN KENAKALAN REMAJA DI SMP N 7 MUARO JAMBI - Anggi Marselina; K.A Rahman; Freddi Sarman (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Adolescence is full of problems and dynamics because this period will find the true identity and self. Adolescents who fail are identical to deviant behavior called juvenile delinquency. Where this juvenile delinquency is caused by peer conformity including culture, personality and social roles. This study aims to determine the relationship between peer conformity and juvenile delinquency at SMPN 7 Muaro Jambi. This study uses a quantitative method with a correlational approach. The population in this study were students of grades VII and VIII of SMPN 7 Muaro Jambi. The sampling technique used random sampling technique with a total of 200 students. Data analysis used correlation through the SPSS IMB 22 program. The results of the study showed that there was a significant relationship between peer conformity and juvenile delinquency in students at SMPN 7 Muaro Jambi, with the results of the correlation analysis getting a result of 0.601 which was in a moderate correlation or capable relationship. The percentage results of the analysis of the peer conformity variable were 54.4% at a moderate level and the percentage results of juvenile delinquency were 76% at a high level.